Benign Mediastinal Lymphadenopathy Presenting as Cor Triatriatum. (7th February 2012) - Noel, Cory V.; Pollard, Jessica; Permut, Lester; Ferguson, Mark; Hattendorf, Brandy
ABSTRACT This report describes a patient with a superior mediastinal mass and extensive intrathoracic lymphadenopathy referred for oncologic care. During her evaluation, an abnormal cardiovascular examination resulted in an echocardiographic evaluation and an unanticipated diagnosis of a highly obstructive left atrial cor triatriatum was uncovered. The patient underwent repair of cor triatriatum and lymph node biopsy shortly after the diagnosis was made. The biopsies revealed reactive lymph nodes with lymphatic dilation and no inflammatory or neoplastic features. To our knowledge, this case represents the first pediatric example of extensive mediastinal lymphadenopathy mimicking the appearance of a malignant process as a result of severe pulmonary venous hypertension.